The Metaphysics of Counselling History on Colonized Land - Clegg, Daniel; Marker, Michael (Canadian Journal of Counselling and Psychotherapy, 2021)
We offer a conceptual analysis of how Canadian counsellor education and counselling psychology can respond to colonial history through the teaching of its own history. Drawing on literature in counselling, education, and decolonial Indigenous scholarship, we work toward a positive and practical way to teach history that addresses power, colonization, and Indigenous intellectual traditions. Those in the fields of Canadian counselling, counsellor education, and counselling psychology are invited to expand their focus on epistemology into an appreciation of being. This focus on being leads to a broadened horizon of counselling as healing education, and a shift towards a place-centred pedagogy of history. It yields a radically different and markedly more humble and pluralistic pedagogy of the history of our field—one that is grounded within the reality of the land.